8 - “University is ISO 9000:2008 Certified”: Neoliberal Echoes, Knowledge Production and Quality Assurance in Kenyan State Universities - Ishmael I. Munene (Journal of Higher Education in Africa, 2013)
In Africa, Quality Assurance (QA) in universities has acquired a sense of urgency owing to the rapid growth of the university sector in the last two decades. The adoption of neoliberal tenets in the development of universities has witnessed the surge in student numbers and types of degree-granting institutions. The decline in budgetary support for higher education, evident in average per-student expenditure decline from US 6,300 to 1,500 by 1990, rising student enrolments coupled with inadequate and outdated teaching and learning resources, alongside massive staff exodus as well as poor governance have raised troubling questions about the quality of education provided. The rising concerns about the quality of the institutions and the graduates have catalyzed national educational authorities and individual institutions to institute quality assurance strategies in order to enhance the quality of education provide. This paper looks at how neoliberalism has undermined faculty validation of learning within the context of QA. Faculty exclusion in knowledge validation via QA is examined from the following themes: national accreditation, ISO certification, internal QA units, internships & attachments, and the deployment of information communication technologies. It is apparent that the development of universities along the neoliberal paradigm has eroded faculty prerogatives in QA as market ideals have triumphed over academic principles.